Case Report: New-Onset Rheumatoid Arthritis Following COVID-19 Vaccination - Watanabe, Tomohiro; Minaga, Kosuke; Hara, Akane; Yoshikawa, Tomoe; Kamata, Ken; Kudo, Masatoshi (Frontiers in Immunology, 2022)
Efficient protection against coronavirus disease 2019 (COVID-19) has been achieved by immunization with mRNA-based vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, efficient immune responses against this novel virus by vaccination are accompanied by a wide variety of side effects. Indeed, flares or new-onset of autoimmune disorders have been reported soon after the COVID-19 vaccination. Although pro-inflammatory cytokine responses play pathogenic roles in the development of autoimmunity, cytokines charactering COVID-19 vaccination-related autoimmune responses have been poorly understood. Given that mRNA derived from COVID-19 vaccine is a potent inducer for pro-inflammatory cytokine responses, these cytokines might mediate autoimmune responses after COVID-19 vaccination. Here we report a case with new-onset rheumatoid arthritis (RA) following COVID-19 vaccination. Serum concentrations not only of arthrogenic cytokines, interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha), but also of type I interferon (IFN) were elevated at the active phase in this case. Induction of remission by methotrexate and tocilizumab was accompanied by a marked reduction in serum concentrations of type I IFN, IL-6, and TNF-alpha.These results suggest that production of type I IFN, IL-6, and TNF-alpha induced by COVID-19 vaccination might be involved in this case with new-onset RA.